COMPARATIVE STUDY OF FASHION AND CONVECTION SMIs IN YOGYAKARTA, SOLO, AND PEKALONGAN - Oktavia, Rina; Wihastuti, Latri; Nurpita, Anisa (Review of Management and Entrepreneurship, 2020)
Industri Kecil dan Menengah (IKM) has an important role in the national economy, especially related to its contribution in employment. IKM is able to create jobs in the informal sector and accommodate workers who are not accommodated in the formal sector. The Ministry of Industry establishes the fashion industry as one of the priority industries that will continue to be developed. One of the supporters of the fashion industry is batik which has a high strength of cultural elements so that it can provide high added value. The cities of Yogyakarta, Solo and Pekalongan are known as the centers of batik in Indonesia. IKM fashion and convection especially batik has become a characteristic and livelihood there. However, the performance of the batik industry in Indonesia, including in these three regions, has recently declined. This study aims to conduct a comparative study of fashion and convection IKM in the cities of Yogyakarta, Solo and Pekalongan. The analytical tool used in this research is descriptive analysis. The results of this study indicate that the three regions have different characteristics.